Islamic education content platform for secondary school students / Norziana Yahya ... [et al.] - Yahya, Norziana; Mohd Yusof, Ernie Mazuin; Hj Ahmad, Ruzita; Md Taib, Mohd Azahani (UiTM Cawangan Perlis, 2021)
The rapid development of information technology has affected various aspects of life including education at the school level. However, conventional teaching and learning methods are still used in secondary schools, especially for Islamic subjects. One of the ways to help students learn better in Islamic subjects is by implementing a web-based content platform in the context of Islamic education. This is a learning tool to support the teaching and learning process using various media such as educational video materials for secondary school students, because multimedia elements will make learning more interesting especially for Islamic subjects that require memorization, reading, and comprehension. Another desired goal is for teachers to be able to manage their Islamic lessons online. In developing web applications, appropriate development methodologies have been implemented using Waterfall Model as a guideline. The waterfall model has different development phases such as analysis, design, implementation, testing and finally documentation. The web-based Islamic Education Content Platform (IECP) was designed and developed using Visual Studio Code with PHP and MySQL databases. It was assessed by obtaining Expert Review (ER) through a set of questionnaires given to four experts and fifteen respondents through User Acceptance Test (UAT). The results of ER indicate that web-based IECP is suitable for use and currently need to be refined and improved. Meanwhile, the UAT results show that web-based IECP is generally accepted and believed to be beneficial, especially to secondary school students and teachers.